The Foxfire Approach: Inspiration for Classrooms and Beyond. - Smith, Hilton (Springer Science and Business Media : SensePublishers, 2016)
"This collection of essays by Foxfire practitioners represents the wide range of adaptations by educators of the pedagogical orientation of the Foxfire Magazine and Foxfire Programs for Teachers. Former students in the magazine class at Rabun County High School share the continuing impact of that experience on their lives, including a former student who is pioneering the magazine project with her sixth grade class. An early childhood teacher make a passionate, articulate case for instruction guided by the Foxfire Core Practices. And a former school administrator shares his experiences as guidance to current school administrators in enabling then supporting teachers to implement instruction guided by Foxfire's Core Practices. Participants in Foxfire's Program for Teachers, from early childhood teachers to college professors, describe their adaptations of the Foxfire Approach for instruction at all grade levels, all subjects and all demographics - including how they coped with the challenges they faced. One practitioner describes how she used the Core Practices to design instruction in rural China. We have an engaging essay focused on our summer courses for teachers, based on extensive observations and interview of participants attending those courses. Several essays explore the pedagogical roots of the Foxfire Approach, as well as its value in providing instruction today which engages the students in the content and results in durable learning. Readers can read straight through the book, beginning with a short historical introductory essay, or skip around to topics of interest to assemble an informed assessment of the potential of the Foxfire Approach."